Orbital Hybridization and Magnetic Coupling at Cuprate–Manganite Interfaces Driven by Manganite Doping. Issue 6 (6th May 2020) - Schlueter, Christoph; Yang, Nan; Mazzoli, Claudio; Cantoni, Claudia; Tebano, Antonello; Di Castro, Daniele; Balestrino, Giuseppe; Orgiani, Pasquale; Galdi, Alice; Herrero‐Martín, Javier; Gargiani, Pierluigi; Valvidares, Manuel; et al.
Abstract: Fundamental understanding of interface mechanisms that generate unexpected physical properties in the cuprate/manganite heterostructures is essential for possible applications as spintronic devices. Here, CaCuO2 /La1− x Sr x MnO3 (CCO/LSMO) superlattices are investigated, where the infinite‐layer cuprate CCO does not have apical oxygen for Cu in the Ca‐plane so that the Mn–O–Cu superexchange coupling can be only present at the MnO2 –(La, Sr)O–CuO2 interface. Two different doping states for the manganites are studied, namely x = 0.1 and x = 0.3, corresponding to the ferromagnetic insulating and ferromagnetic metallic states, respectively, in the manganite phase diagram. Linear and circular dichroism in X‐ray absorption by synchrotron radiation at Cu and Mn L‐edges clearly demonstrate that in the absence of apical oxygen in the cuprate block, the magnetic coupling between the LSMO and CCO is weakly ferromagnetic when LSMO is metallic, while it is antiferromagnetic when LSMO is insulating, along with an increased Cu 3d(3 z 2 – r 2 ) and Mn 3d(3 z 2 – r 2 ) orbital occupation. It is proposed that the Mn 3d valence band upward shift driven by the enhancement of Mn 3+ content in the underdoped sample enhances the orbital hybridization. The stronger hybridization at the interface MnO2 –(La, Sr)O–CuO2 gives rise to the antiferromagnetic coupling between cuprate and underdoped manganite. Abstract : The cuprate/manganite interface shows different magnetic coupling depending on the manganite doping. The magnetic coupling is ferromagnetic or antiferromagnetic when the manganite is optimally doped or underdoped, respectively. The higher overlap of Cu 3d and Mn 3d bands driven by the larger Mn 3+ content in the underdoped manganite facilitates the antiferromagnetic coupling between Cu 3d(3 z 2 – r 2 ) and Mn 3d(3 z 2 – r 2 ) orbitals.